ACADEMIC INNOVATION TO IMPROVE RELATIONS Univeridad - NOW. - Silva Toledo, Victor (1998)
Currently Facing Globalization of the World Economy, particularly in our country, has motivated both Transnational companies like National adopt attitudes of change in their organizations. These changes result in the search for competitiveness in a free market; why require the human potential for the Third Millennium, be prepared not only basic knowledge, attitudes and skills but with revealing knowledge of the business environment; and any change of mind to deal with both the Supplier and the Customer that are in the market for the Company.